Metacognição e emoções no ensino remoto emergencial - Lima, Thaynna Sandy Souza (Universidade Federal Rural do Semi-Árido, 2021)
Metacognition, a construct understood as the awareness of one's own cognitive functioning, allows the individual to use this knowledge to achieve goals, manage difficulties and selfregulate, being widely studied in the field of education due to its importance for the process of learning. Emotions also play an important role in human learning, as they guide the individual's behaviour, needs, interests and motivations and are responses to stimuli, which can guide metacognitive self-monitoring processes or permeate metacognitive experiences. These two dimensions are relevant to understand the student experience during emergency remote teaching (ERE). This teaching modality was implemented because of the COVID-19 pandemic, which had repercussions on this and other changes to society's ways of life. With this, the objective of this work was to analyse the relations between metacognition and emotional aspects of undergraduate students with their experiences and study conditions in the ERE. It was characterized as a transversal and descriptive research, with a quantitative approach, developed with undergraduate students from the four campuses of the Federal Rural University of the Semi-Árido (UFERSA). From this population, considering students with active enrolment and over 18 years old, excluding students who locked out all enrolled subjects and adopting a non-probabilistic sampling with a confidence level of 95% and a margin of error of 6 %, a sample of 329 students was arrived at. The instruments used were the following: a socio-biodemographic questionnaire on the profile of students, their means of access to online classes and academic activities, their currently environment to study, their experiences and emotions related to the educational processes in this semester; and an instrument for evaluating metacognitive strategies and emotional aspects. Data were collected online using the Google Forms tool and statistically analysed. Regarding the profile of the participants, there is a balance between women (47.72%) and men (52.28%), with an average age marked by young adults (±25.04), predominantly single (55.62%) and less than half develop some work activity or internship (39.52%). The results showed significant interrelationships between metacognition and emotional aspects and some conditions for the study and student experiences during the ERE. It was observed that the students had difficulties in relation to the internet and the home environment, relating to metacognition and emotional aspects. The metacognitive strategies of self-monitoring and self-regulation were shown to be related to the students' experiences, providing them with resources for the analysis of cognitive and academic needs and for managing demands. Emotions also showed to be related to these experiences, permeating the student's perception of their external and internal resources for academic performance. Thus, it was concluded that metacognition and emotional aspects are related to positive experiences of students and that they can contribute not only to academic performance, but to a more integral stimulation of the student involving the social and emotional factors that permeate learning
Keywords: Metacognição; Emoções; Universitários; Pandemia; Ensino remoto emergencial; Metacognition; Emotions; Undergraduates; Pandemic; Emergency remote teaching; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES